Environmental Variability and Cyanobacterial Blooms in a Subtropical Coastal Lagoon: Searching for a Sign of Climate Change Effects - de Souza, Márcio S.; Muelbert, José H.; Costa, Luiza D. F.; Klering, Eliana V.; Yunes, João S. (Frontiers in Microbiology, 2018)
Cyanobacterial blooms in marine and freshwater environments may be favored by shifts in physical water column parameters due to increasing temperature under climate change. The Patos Lagoon (PL), a subtropical coastal environment in southern Brazil, is known for recurrent blooms of Microcystis aeruginosa complex (MAC). Here, we analyze the variability of these blooms and their relation to changes in wind direction and speed, rainfall and freshwater run-off from 2000 to 2017. Also, we discuss both longer time-series of air temperature and rainfall and a review of local studies with microcystins produced by these noxious species. Since the 1980s, MAC blooms were associated to negative anomalies in annual precipitation that occur during La Niña periods and, in the last years (2001–2014), accompanied by a trend in low river discharge. MAC blooms were conspicuous from December to March, i.e. austral summer, with massive patches seen in satellite images as for 2017. We suggest that low rainfall and run-off years under NE wind-driven hydrodynamics might accumulate MAC biomass in the west margin of the PL system. In contrast, a positive, long-term trend in precipitation (from 1950 to 2016; slope=3.9868mm/yr, p<0.05) should imply in high river discharge and, consequently, advection of this biomass to the adjacent coastal region. Due to the proximity to urban areas, the blooms can represent recreational and economic hazards to the region.